2020
DOI: 10.1177/0038038520929540
|View full text |Cite
|
Sign up to set email alerts
|

Left Behind in the Hungarian Rustbelt: The Cultural Political Economy of Working-Class Neo-Nationalism

Abstract: Nationalism is back with a renewed force. Hungary is a virulent example of the new nationalist ascendancy. As the country was a former liberal star pupil, Hungary’s neo-nationalist turn has been puzzling researchers for years. This study goes beyond the entrenched polarisations in the literature by highlighting the dynamic interplay between culture, structure and identity. It proposes to conceptualise Hungary’s neo-nationalist turn as a Polanyian countermovement against commodification, globalisation and deind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 47 publications
(44 reference statements)
0
13
0
1
Order By: Relevance
“…Shrining rustbelt towns evoke a sense of loss, depression, spatial stigma, and trauma. The loss of working-class culture and identity has also been associated with the rise of nationalism is rustbelt towns (Scheiring 2020).…”
Section: Deaths Of Despair In Hungary's Rustbeltmentioning
confidence: 99%
See 1 more Smart Citation
“…Shrining rustbelt towns evoke a sense of loss, depression, spatial stigma, and trauma. The loss of working-class culture and identity has also been associated with the rise of nationalism is rustbelt towns (Scheiring 2020).…”
Section: Deaths Of Despair In Hungary's Rustbeltmentioning
confidence: 99%
“…The collapse of state socialism also led to a particularly violent form of ideological and symbolic displacement of workers (Kalb 2019;Kideckel 2008;Ost 2000;Scheiring 2020;Stenning 2005). The rise of neoliberal consumer culture contributed to the loss of working-class solidarity.…”
Section: Deaths Of Despair In Hungary's Rustbeltmentioning
confidence: 99%
“…6 To reduce the bias resulting from the fluctuation in the second half of the 1980s, we compare death rates to 1980. those who kept their job but experienced higher workload and decreased control at work were at higher risk of dying (Lundberg et al 2007;Pikhart et al 2001). Qualitative research also revealed that deindustrialization in former socialist industrial towns led to social disintegration, status loss, the loss of communities, and a cascade of infrastructural, social, and health problems, depression, prolonged stress, and despair both in Russia and Hungary (Hegedűs 2010;Kideckel 2008;Parsons 2014;Scheiring 2020a). Growing depressive symptoms, despair, and distress were also robustly correlated with Hungarians' increased mortality (Kopp et al 2000;Kopp et al 2007).…”
Section: Dislocation-despair Contra Alcohol Supply and Culturementioning
confidence: 99%
“…Russian enterprises spent around 3-5 percent of GDP on social provision, while East European firms spent about half this amount, which is still very significant (Cook 2007:39-40). Industrial employment also contributed to social integration, vibrant work-and neighborhood communities (Kideckel 2002;Scheiring 2020a). Thus, although industrial working class culture also harbored adverse lifestyles such as drinking (Carlson and Hoffmann 2011;Cockerham et al 2002), industrial plants also contributed to health and wellbeing in many ways.…”
Section: Deindustrialization Stress and Despairmentioning
confidence: 99%
“…Orbán’s decade in power has been characterised in terms of ‘democratic backsliding’ (Cianetti et al . 2018 ; Scheiring 2021 ) and ‘illiberalism’ (Wilkin 2018 ; Scheiring 2020b ). 4 My approach interprets the 2010s as a new phase of embeddedness, following an exemplary Polanyian double movement.…”
mentioning
confidence: 99%